HUBUNGAN TINGKAT PENGETAHUAN TENTANG KARIES GIGI DENGAN PERILAKU PERAWATAN GIGI PADA ANAK KELAS 3-4 DI SDN BARATAN 01 KABUPATEN JEMBER - Ahmad Efrizal Ammrullah; Mahmud Ady Yuwanto (Jurnal Kesehatan dr. Soebandi, 2017)
The problem of dental and mouth infections that are still common in Indonesia, one of which is dental caries. One of the age groups that often experience these disease problems is the elementary school age group. One of the factors that influence is knowledge and awareness of the importance of dental care. In the year 2015 in East Java that received dental health services was 19,549 people. And those who need to get dental treatment are 558,241 people. The design of this study uses a correlational cross sectional approach that researchers can search for, explain the relationship and test between 2 variables, namely the level of knowledge about dental caries with dental care behavior. Population in this study were 35 children , while the sample of 32 children. The sampling technique used was simple random sampling. The results of this study indicate that the majority of respondents (43.8%) have less knowledge and a small portion (12.5%) respondents have good knowledge. While the dental treatment behavior of the majority (46.9%) of respondents behaved less and a small portion (25.0%) of respondents behaved well. Data analysis test uses the Spearman rank with p value 0.00 <α 0.05 which means there is a relationship between the level of knowledge about dental caries with dental care behavior. Providing information by educational institutions, health institutions and parents to improve information related to dental caries and care teeth in school-age children so as to prevent dental caries. It is assumed that a person's behavior is a manifestation of everything he knows.